Changing the Students’ Mind-set via Sustainability - Issa, Tomayess (2017)
This chapter discusses and examines the integration of a sustainability unit in the higher education curriculum in Western Australia. The Information Technology Seminar 65 (ITS65) unit was developed subsequent to the repercussions of the global financial crisis in 2007–2008 which saw businesses and users struggling to survive, especially in the area of information technology/systems. The ITS65 unit aims to provide students with an understanding, knowledge and experience of Organizational Sustainable Strategy and Green IT. This chapter will examine whether the completion of the ITS65 unit can transform students’ mindset. This chapter provides empirical evidence based on quantitative and qualitative data derived from two sources. The first is the anonymous informal feedback collected during the semester, while the second (the formal) is the other anonymous online system for gathering and reporting students’ perceptions of their learning experiences at the university. Evaluations of and attitudes to the ITS65 unit were collected from 89 out from 127 students via the university’s ‘eVALUate’ system. Finally, students’ comments indicate that their completion of the ITS65 unit changed their mindset and made them more aware of sustainability and Green IT, and their moral responsibility for the natural environment.